Application of the modified Cam-Clay model to a residual soil - Lodi, P. C.; Machado, S. L.; Vilar, O. M. (A A Balkema Publishers, 2000)
The modified Cam - Clay model was used to model experimental results of a saturated residual sandy soil from Sao Carlos - SP. Triaxial compression tests were performed using Bishop - Wesley cell with internal transducers to measure axial and radial strains. It was observed that the model fairly fitted experimental results, specially the principal stress difference at critical state. In general it was observed a good qualitative agreement between experimental and predicted strain values, considering compression or expansion of the samples. However, in all the stress path used, but 100 degrees and 140 degrees, the model yielded strains larger than that measured in the tests.